2017
DOI: 10.12973/ejmste/77946
|View full text |Cite
|
Sign up to set email alerts
|

Factors and Levels Associated with Lecturers’ Motivation and Job Satisfaction in a Chinese University

Abstract: Motivation and job satisfaction of employees have been an important research area in recent years. Based on a case study on two-new-established colleges in one university located in China Beijing town, this study aimed to correlate and investigate the levels and factors affecting lecturers' motivation and job satisfactions in this university. The descriptive survey and co-relational methods were used. Seventy lecturers with 51.4 % male and 48.6 % female participated in the study. Data were analyzed by frequenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 23 publications
1
13
0
Order By: Relevance
“…Findings from all data collected showed how there are other different factors such the expectation of good job (Deci and Ryan, 1985;Hoy and Miskel, 1987;Pennington, 1995;Beck, 1983;Wigfield and Eccles, 2000), promotion (Munyengabe et al, 2016;Wanga and Xiao, 2017), social pressure and shame of returning home empty hands (Altbach, 2004;Khadria, 2011). International PhD students also expressed the high motivation to pursue PhD studies because of the expectation of social respect paid to PhD' holders in their respective countries.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Findings from all data collected showed how there are other different factors such the expectation of good job (Deci and Ryan, 1985;Hoy and Miskel, 1987;Pennington, 1995;Beck, 1983;Wigfield and Eccles, 2000), promotion (Munyengabe et al, 2016;Wanga and Xiao, 2017), social pressure and shame of returning home empty hands (Altbach, 2004;Khadria, 2011). International PhD students also expressed the high motivation to pursue PhD studies because of the expectation of social respect paid to PhD' holders in their respective countries.…”
Section: Discussionmentioning
confidence: 99%
“…Such research exploring what motivates students to pursue PhD studies in Mathematics and sciences studies is among of important research area to illustrate all challenging situations and feasibility of the current international student mobility (OECD, 2012). Regardless different factors related to participants characteristics such as: age, gender, family background, cultural diversities, social pressures and many other different barriers; it is shown that the success to meet the graduation requirements for international PhD students explains the great importance of being motivated to achieve their targets (Piché, 2003;Deci and Ryan, 1985;Weiner, 1992;Munyengabe et al, 2017b).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Mertler (2002) however found out in the United States that 77% of the survey respondents were generally satisfied and motivated by performing their duties as teachers. Again, Munyengabe et al (2017) established from a study that levels of motivation of lecturers in Chinese University was satisfactory. Dorji (2014) also concluded from a study that teachers in government and middle secondary schools in Thimphu were moderately motivated.…”
Section: Introductionmentioning
confidence: 99%